Intraoperative assessment of cerebral blood flow changes in normal and pathological brain tissue using an infrared camera. Issue 2 (3rd July 2018) - Zębala, Marta; Kaczmarska, Katarzyna; Bogucki, Jacek; Kastek, Mariusz; Piątkowski, Tadeusz; Polakowski, Henryk; Przykaza, Łukasz; Koźniewska, Ewa; Koszewski, Waldemar; Czernicki, Zbigniew
Abstract: This study attempted to evaluate brain surface temperature using infrared thermography in patients with brain tumours, in particular those located in the vicinity of the eloquent areas. The clinical part of the study was preceded by the experiments on rats undertaken to test time-relation of cerebrocortical microflow (LDF) and brain surface temperature changes using the same infrared camera as in the clinical study. A significant positive correlation ( r  = 0.88, p  < 0.05) between the maximum microflow changes and maximum brain temperature changes was observed. The temperature changes occurred, however, with some delay in comparison with LDF changes. In the clinical study, temperature was recorded before, during and after removal of a tumour in fifteen patients and an abscess in one patient. In patients with tumours located close to eloquent areas, temperature distribution was also measured during the awake part of the surgical procedure. The temperature of the tumour was different from the temperature of the tissues adjacent to the resected pathology. In four patients subjected to the intraoperative awake procedure, the temperature increase in the activated motor cortex region was observed. For the first time, it was possible to identify the cortical arteries supplying the eloquent areas.